Analisis Manfaat Komik Pendidikan Legenda Pulau Penyengat Sebagai Media Pembelajaran Iklan di Kelas VIII SMPN 5 Tanjungpinang - Anggi Novita Manalu; Elsita Putri Yani; Fia Nur Amanah; Mila Permata Sari; Maulida Mustado; Rita Selvina Simatupang (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the benefits of using the educational comic Legenda Pulau Penyengat as a learning medium for advertisement materials in eighth-grade students of SMP Negeri 5 Tanjungpinang. The background of this research is based on the low level of students’ interest and understanding of advertisement materials when taught using conventional teaching methods. Therefore, innovative, interesting, and contextual learning media are needed to improve the effectiveness of the learning process. Educational comics are chosen because they present learning materials in visual and narrative forms that are easier for students to understand. This study employed a qualitative descriptive method, with data collected through observation, interviews, and documentation during the learning process. The results indicate that the use of the educational comic Legenda Pulau Penyengat increases students’ learning interest, understanding of advertisement concepts, and ability to identify the elements and language of advertisements. In addition, this comic helps students connect learning materials with local cultural values. Thus, the educational comic Legenda Pulau Penyengat can be considered an effective alternative learning medium for teaching advertisements in junior high school.